2018
DOI: 10.1155/2018/2010675
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Mechanisms of Selective PPARγ Modulators in Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is a chronic neurodegenerative disease characterized by abnormal protein accumulation, synaptic dysfunction, and cognitive impairment. The continuous increase in the incidence of AD with the aged population and mortality rate indicates the urgent need for establishing novel molecular targets for therapeutic potential. Peroxisome proliferator-activated receptor gamma (PPARγ) agonists such as rosiglitazone and pioglitazone reduce amyloid and tau pathologies, inhibit neuroinflammation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 185 publications
(181 reference statements)
0
31
0
3
Order By: Relevance
“…Nowadays, the agonist of PPAR gamma (PPARγ) is promising treatment for neuroinflammation-related condition eg. Alzheimer's disease, Parkinson's disease, and stroke (Govindarajulu et al, 2018 ; Wen et al, 2018 ; Lee et al, 2019 ). It was demonstrated that PPAR attenuated the release of pro-inflammatory cytokines and oxidative stress promotors.…”
Section: Hiv-1 and Glutamate Neurotoxicity—the Role Of Glutamate Recementioning
confidence: 99%
“…Nowadays, the agonist of PPAR gamma (PPARγ) is promising treatment for neuroinflammation-related condition eg. Alzheimer's disease, Parkinson's disease, and stroke (Govindarajulu et al, 2018 ; Wen et al, 2018 ; Lee et al, 2019 ). It was demonstrated that PPAR attenuated the release of pro-inflammatory cytokines and oxidative stress promotors.…”
Section: Hiv-1 and Glutamate Neurotoxicity—the Role Of Glutamate Recementioning
confidence: 99%
“…Although evidence suggests that peroxisome proliferator-activated receptor γ (PPARγ) modulators like thiazolidinediones (TZD) improve neuroinflammation and synaptic plasticity [86], the detailed mechanism for these effects is yet to be explored [87]. However, insulin is generally regarded as safer due to the adverse effects of TZDs on other organ systems.…”
Section: Role Of Apoe In Brain Insulin Signaling and Glucose Metabolismmentioning
confidence: 99%
“…The latter, complement reports that animal models of diabetes exhibit cognitive impairments and features of AD neuropathology (Clodfelder-Miller et al, 2006). Together, these data make it plausible that AD may be amenable to antidiabetic treatments (for review, see Govindarajulu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%